USAHA GURU PENDIDIKAN AGAMA ISLAMDALAM MENGEMBANGKAN KECERDASANINTERPERSONAL SISWA DISMPN 06 SINGINGI HILIR - Misri Susanti; Sopiatun Nahwiyah; Andrizal Andrizal (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Misri Susanti: Islamic religion teacher education efforts in developingl Interpersonal Intelligence of Students in Junior High School 06 singingi Hilir. The background Problem of researchers are interested in wanting to know the effots of teachers in developing Interpersonal Intellingence in stdens in junior high school 06 singingi Hilir . As for the formulation of the problem of this research is how the efforts of islamic religious education teachers in developing Interpersonal intellingence of students in Junior hing School 06 singingi Hilir downstream, the factors that influence the efforts of islamic religious education teacers and their students in junior 06 Singingi Hilir.This research was conducted in junior High School 06 downstream singingi Hilir. Data collection techingues throungh interview Studies, Observation, dokumentation. And furthermore the researchers analyzed the data collection was carried out bay submitting interviews whits respondents of islamic religious education teachers and studens in Jubior high school singingi Hilir.The result showed that there was a very good effort in islamic religiousieducation teachers, namley through giving advice to their students, lingking the matrial with their environment praying before learning, alway getting used to the midday prayer in cougregation and playing a role in the method of islamic religion education teachers were able to increase stimulation in Studens wiil be the development of students in junior high scools singingi hilir. Interpersonal intelligence of studens such as the ability to understand themseleves , aawareness of moods, and motivate students and self siscipline ability. Then the factors that influ ence the existence of student intellingence include self factor family, factor community. Kata Kunci: Usaha Guru, Kecerdasan Interpersonal Siswa